2017
DOI: 10.1137/17m1117598
|View full text |Cite
|
Sign up to set email alerts
|

Bohr's Correspondence Principle for the Renormalized Nelson Model

Abstract: In the mid Sixties Edward Nelson proved the existence of a consistent quantum field theory that describes the Yukawa-like interaction of a non-relativistic nucleon field with a relativistic meson field. Since then it is thought, despite the renormalization procedure involved in the construction, that the quantum dynamics should be governed in the classical limit by a Schrödinger-Klein-Gordon system with Yukawa coupling. In the present paper we prove this fact in the form of a Bohr correspondence principle. Bes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 125 publications
2
49
0
Order By: Relevance
“…In the theorem we also provide bounds for the specific initial state N j=1 ϕ 0 j ⊗W (N 2/3 α 0 )Ω. Since for this state γ (1,0)…”
Section: Proof Of Theorem Ii3mentioning
confidence: 99%
“…In the theorem we also provide bounds for the specific initial state N j=1 ϕ 0 j ⊗W (N 2/3 α 0 )Ω. Since for this state γ (1,0)…”
Section: Proof Of Theorem Ii3mentioning
confidence: 99%
“…A comparison between his result and Theorem III.3 is given in Remark III.4. Making use of a Wigner measure approach Ammari and Falconi [1] were able to establish the classical limit (without quantitative bounds on the rate of convergence) of the renormalized Nelson model without cutoff. Teufel [27] considered the adiabatic limit of the Nelson model and showed that the interaction mediated by the quantized radiation field is well approximated by a direct Coulomb interaction.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…These involve fewer degrees of freedom, are less exact but easier to investigate. Effective evolution equations for particles that interact with quantized radiation fields have rigorously been derived for example in [9,6,1,27,7,8,14,10]. The general setting in these works is given by the tensor product of two Hilbert spaces…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations